2015
DOI: 10.1016/j.pocean.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Photoheterotrophy of bacterioplankton is ubiquitous in the surface oligotrophic ocean

Abstract: Accurate measurements in the Southern Hemisphere were required to test a hypothesis of the ubiquity of photoheterotrophy in the oligotrophic ocean. We present experimental results of light-enhanced uptake of methionine, leucine and ATP by bacterioplankton during two large-scale transects of the South Atlantic. Light increased the uptake of substrates by both dominant bacterioplankton groups: Prochlorococcus and SAR11, as well as for the bulk microbial community. Our consistent experimental evidence strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The dominant genera, Prochlorococcus and Synechococcus, are known to take up amino acids (Church et al, 2004;Zubkov et al, 2003Zubkov et al, , 2004Zubkov et al, , 2008Michelou et al, 2007;Mary et al, 2008;Gómez-Pereira et al, 2013;Evans et al, 2015), glucose (Gómez-Baena et al, 2008;Muñoz-Marín et al, 2013) and dimethylsulfoniopropionate (Vila-Costa et al, 2006), and analysis of 12 genomes has shown that certain strains have genes for amino acid, sugar, oligopeptide and phosphonate uptake (Rocap et al, 2003;Martiny et al, 2006;Kettler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant genera, Prochlorococcus and Synechococcus, are known to take up amino acids (Church et al, 2004;Zubkov et al, 2003Zubkov et al, , 2004Zubkov et al, , 2008Michelou et al, 2007;Mary et al, 2008;Gómez-Pereira et al, 2013;Evans et al, 2015), glucose (Gómez-Baena et al, 2008;Muñoz-Marín et al, 2013) and dimethylsulfoniopropionate (Vila-Costa et al, 2006), and analysis of 12 genomes has shown that certain strains have genes for amino acid, sugar, oligopeptide and phosphonate uptake (Rocap et al, 2003;Martiny et al, 2006;Kettler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Prochlorococcus genomes contain genes encoding the ability to utilize organic compounds including amino acids (Zubkov et al ; Rocap et al ; Church et al ; Michelou et al ; Mary et al ), as well as glucose transporters (Rocap et al ; Gómez‐Baena et al ; Muñoz‐Marín et al ). Recent studies have also shown that Prochlorococcus is able to take up glucose and amino acids in both light and dark conditions—in laboratory cultures and in the wild (Zubkov et al ; Church et al ; Michelou et al ; Gómez‐Baena et al ; Mary et al ; Gómez‐Pereira et al ; Muñoz‐Marín et al 2013; Evans et al )—as well as dimethylsulfoniopropionate (Vila‐Costa et al ). Amino acids could be used as either a carbon, energy, or nitrogen source, but glucose is likely only utilized for carbon and/or energy.…”
mentioning
confidence: 99%
“…Inorganic tripolyP was also bioavailable to coastal phytoplankton communities examined in one field study (Björkman and Karl ). PolyP from NTPs appear to be widely bioavailable and may be the most labile form of polyP (Moore et al ; Michelou et al ; Mazard et al ; Duhamel et al ; Evans et al ). Overall, previous studies suggest that organic and inorganic short‐chain polyP (tripolyP) are bioavailable to laboratory‐grown cyanobacteria and field populations of coastal phytoplankton.…”
mentioning
confidence: 99%